How People Domesticated Amazonian Forests - Levis, Carolina; Flores, Bernardo M.; Moreira, Priscila A.; Luize, Bruno G.; Alves, Rubana P.; Franco-Moraes, Juliano; Lins, Juliana; Konings, Evelien; Peña-Claros, Marielos; Bongers, Frans; Costa, Flavia R. C.; Clement, Charles R. (Frontiers in Ecology and Evolution, 2018)
For millennia, Amazonian peoples have managed forest resources, modifying the natural environment in subtle and persistent ways. Legacies of past human occupation are striking near archaeological sites, yet we still lack a clear picture of how human management practices resulted in the domestication of Amazonian forests. The general view is that domesticated forests are recognizable by the presence of forest patches dominated by one or a few useful species favored by long-term human activities. Here, we used three complementary approaches to understand the long-term domestication of Amazonian forests. First, we compiled information from the literature about how indigenous and traditional Amazonian peoples manage forest resources to promote useful plant species that are mainly used as food resources. Then, we developed an interdisciplinary conceptual model of how interactions between these management practices across space and time may form domesticated forests. Finally, we collected field data from 30 contemporary villages located on and near archaeological sites, along four major Amazonian rivers, to compare with the management practices synthesized in our conceptual model. We identified eight distinct categories of management practices that contribute to form forest patches of useful plants: (1) removal of non-useful plants, (2) protection of useful plants, (3) attraction of non-human animal dispersers, (4) transportation of useful plants, (5) selection of phenotypes, (6) fire management, (7) planting of useful plants, and (8) soil improvement. Our conceptual model, when ethnographically projected into the past, reveals how the interaction of these multiple management practices interferes with natural ecological processes, resulting in the domestication of Amazonian forest patches dominated by useful species. Our model suggests that management practices became more frequent as human population increased during the Holocene. In the field, we found that useful perennial plants occur in multi-species patches around archaeological sites, and that the dominant species are still managed by local people, suggesting long-term persistence of ancient cultural practices. The management practices we identified have transformed plant species abundance and floristic composition through the creation of diverse forest patches rich in edible perennial plants that enhanced food production and food security in Amazonia.